PENDISTRIBUSIAN DANA ZAKAT PRODUKTIF DI BADAN AMIL ZAKAT NASIONAL (BAZNAS) KOTA JAMBI - Habriyanto; Ahsan Putra Hafiz; Fitalia Maharani (CV. KAMPUS AKADEMIK PUBLISING, 2023)
: Fund distribution is the activity of distributing funds from officers to people who are entitled to receive them in accordance with applicable regulations. The purpose of this study was to determine the mechanism for distributing productive zakat funds in BAZNAS Jambi City and to find out what are the inhibiting and supporting factors in the distribution of productive zakat funds in BAZNAS Jambi City. The method used in this research is qualitative descriptive. Data collection for this research was carried out by conducting observations, interviews and documentation. The validity test used in this research uses triangulation techniques. Based on the results of this research, it shows that the mechanism for distributing productive zakat funds in BAZNAS Jambi City has two patterns, namely the traditional productive zakat distribution pattern and the creative productive zakat distribution pattern. Prospective mustahik who wish to receive productive zakat must first submit an application to BAZNAS Jambi City by completing the requirements provided by BAZNAS Jambi City. Inhibiting factors in distributing productive zakat funds in BAZNAS Jambi City include wide reach, there are mustahik who do not understand productive zakat, and human resources. Supporting factors in the distribution of productive zakat funds in BAZNAS Jambi City include the existence of a clear program design and the availability of zakat funds